2020
DOI: 10.1155/2020/8847812
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiotic Resistance Patterns of Ocular Bacterial Strains Isolated from Pediatric Patients in University Hospital of Campania “Luigi Vanvitelli,” Naples, Italy

Abstract: Eye infections caused by bacteria are a serious public health problem among pediatric patients. These diseases, if not properly treated, can cause blindness and impaired vision. The study aimed to evaluate the antimicrobial resistance profiles of the main pathogens involved in eye infections. This study involved pediatric patients enrolled at the “Luigi Vanvitelli” University Hospital of Campania in Naples, Italy, between 2017 and 2019. Of a total of 228 pediatric patients, 73 (32%) tested positive for bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
2
13
2
Order By: Relevance
“…We observed a higher occurrence of conjunctivitis in male (65%) when compared to female (35%) patients. A similar result was observed in an Italian independent study by Petrillo et al [ 19 ]. In this study, the results of culture and PCR methods revealed the occurrence rate of 1% for M. catarrhalis in conjunctivitis samples.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed a higher occurrence of conjunctivitis in male (65%) when compared to female (35%) patients. A similar result was observed in an Italian independent study by Petrillo et al [ 19 ]. In this study, the results of culture and PCR methods revealed the occurrence rate of 1% for M. catarrhalis in conjunctivitis samples.…”
Section: Discussionsupporting
confidence: 91%
“…In a study by Jyoti et al [ 22 ] from India, the prevalence of M. catarrhalis was reported as 0.4% in conjunctivitis specimens that was lower than this study. In previous reports from various countries of the world, the coagulase-negative Staphylococci and S. aureus were among the most prevalent species isolated from eye infections, including conjunctivitis [ 17 , 19 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, as described by Petrillo F. et al, a higher incidence of CoNS (60.4%) eye infections was reported among pediatric patients. CoNS were considered a part of commensal skin flora, so their presence was dismissed as sampling contamination, but in recent years, they have been reported as human pathogens that cause ocular infections in patients with clinical symptoms [ 4 ]. In the present study, methicillin-resistance was reported in 61.7% among CoNS isolates.…”
Section: Discussionmentioning
confidence: 99%
“…However, some conditions, such as prolonged and improper use of contact lenses, surgery, trauma, previous ocular infections, dry eye state, nasolacrimal duct obstructions or reduced host defense, can cause several ocular infections by adapted microorganisms [ 2 , 3 ]. Bacteria are responsible for about 32–74% of ocular infections, followed by viruses, fungi and parasites [ 4 , 5 ]. Worldwide people of all age and genders can have bacterial eye infections that include keratitis, dacryocystitis, endophthalmitis, blepharitis and conjunctivitis [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This report should serve as a public health warning signal, however, to intensify surveillance efforts and identify mcr-1 tanks in sensitive populations. Environmental, food and clinical monitoring are essential in order to reduce the transfer of multi-strain resistant bacteria between animals and humans Finally, increased vigilance and the implementation of antimicrobial management programs are necessary and important in the health sector to slow the spread of antimicrobial resistance [22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%